Steel plates and welded joints

By optimizing the chemical composition and microstructure of DP steel sheets, including controlled Mn segregation, the challenge of maintaining welded joint strength in high-strength DP steel sheets is addressed, achieving both high tensile strength and excellent formability.

JP7659207B2Active Publication Date: 2025-04-09NIPPON STEEL CORPORATION
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023508799
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-25
Filing Date
2022-02-18
Publication Date
2025-04-09
Estimated Expiration
2042-02-18

AI Technical Summary

Technical Problem

High-strength Dual Phase (DP) steel sheets with tensile strength of 980 MPa or more face a challenge in maintaining the strength of welded joints, as coarse martensite in the heat-affected zone leads to residual stresses and cracking.

Method used

The steel sheet is formulated with a specific chemical composition and microstructure, including ferrite, bainite, and martensite, with controlled Mn segregation to prevent coarse austenite formation in the heat-affected zone, thereby enhancing welded joint strength.

Benefits of technology

The solution achieves a tensile strength of 980 MPa or more while maintaining excellent formability and ensuring sufficient strength in welded joints, as evidenced by a maximum old γ particle diameter less than 30 μm in the heat-affected zone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659207000009
    Figure 0007659207000009
  • Figure 0007659207000010
    Figure 0007659207000010
  • Figure 0007659207000011
    Figure 0007659207000011
Patent Text Reader

Abstract

This steel sheet has a predetermined chemical composition, and has, at a t / 4-position which is a position at a distance of t / 4 from the surface in a sheet thickness direction cross section when the sheet thickness is defined as t, a metal structure including 20% or more of ferrite and a total of 40% or more of bainite and martensite in volume fraction, the remaining portion being at least one selected from retained austenite and perlite. In a square-shaped area in which the length of one side is t / 4 and which is centered at the t / 4-position in the sheet thickness direction cross section, when the Mn concentration is measured at multiple measurement points located apart at a 1 μm-interval, the proportion of measurement points in which the Mn concentration is at least 1.1 times of the average value of the Mn concentration at all the measurement points is less than 10.0%. The steel sheet has a tensile strength of 980 MPa or more. The product between the tensile strength and the total elongation of the steel sheet is 10500 MPa·% or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel plate and a welded joint. This application claims priority based on Japanese Patent Application No. 2021-051017, filed on March 25, 2021, the contents of which are incorporated herein by reference. [Background technology]

[0002] In recent years, there has been a demand for improved fuel efficiency in automobiles in light of the regulations on greenhouse gas emissions as part of global warming countermeasures, and the use of high-strength steel sheets is becoming more and more widespread in order to reduce the weight of automobile bodies and ensure collision safety. In particular, there has been an increasing need for high-strength steel sheets with a tensile strength of 980 MPa or more.

[0003] High-strength steel sheets for automotive parts are required to have not only strength but also properties necessary for part forming, such as press formability. Properties necessary for press formability include ductility (elongation). Therefore, there is an increasing need for steel sheets that have both high strength and excellent ductility.

[0004] Dual phase steel sheet (hereinafter referred to as DP steel), which is mainly composed of a composite structure of a soft ferrite phase and a hard martensite phase, is known as a steel sheet that can obtain excellent ductility (for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 6-128688 [Patent Document 2] Japanese Patent No. 5305149 Summary of the Invention [Problem to be solved by the invention]

[0006] As mentioned above, in the field of automobiles, there is a growing need for high-strength steel sheets with excellent formability, especially in recent years. However, in recent years, there has been an issue that DP steels with a tensile strength of 980 MPa or more may have low weld joint strength when welded. In response to such problems, Patent Documents 1 and 2 disclose DP steel, but do not consider the strength of the welded joint. Thus, there has been no technology proposed to improve the strength of the welded joint of DP steel with a tensile strength of 980 MPa or more.

[0007] An object of the present invention is to provide a steel plate having excellent formability and a tensile strength of 980 MPa or more, which has sufficient welded joint strength after welding, and a welded joint obtained from the steel plate, which has sufficient welded joint strength. [Means for solving the problem]

[0008] The present inventors have investigated the cause of the decrease in strength of welded joints when welding DP steels with a tensile strength of 980 MPa or more. As a result, it was found that when coarse martensite exists in the heat-affected zone, residual stress occurs in the plate thickness direction, and cracks easily occur in the vicinity of the coarse martensite. Furthermore, as a result of further investigations, the present inventors have found that suppressing Mn segregation is effective in suppressing the coarsening of prior γ grain size in the heat-affected zone.

[0009] The present invention has been made in view of the above findings. [1] A steel sheet according to one embodiment of the present invention has, by mass%, C: 0.05% or more and 0.25% or less, Si: 0.05% or more and 2.00% or less, Mn: 1.50% or more and 3.00% or less, Al: 0.005% or more and 1.500% or less, P: 0% or more and 0.040% or less, S: 0% or more and 0.010% or less, N: 0% or more and 0.0100% or less, O: 0% or more and 0.0060% or less, Cr: 0% or more and 0.50% or less, Ni: 0% or more and 1.00% or less, Cu: 0% or more and 1.0 0% or less, Mo: 0% or more, 0.50% or less, Ti: 0% or more, 0.200% or less, Nb: 0% or more, 0.200% or less, V: 0% or more, 0.500% or less, B: 0% or more, 0.0100% or less, W: 0% or more, 0.1000% or less , Ta: 0% or more, 0.1000% or less, Sn: 0% or more, 0.0500% or less, Co: 0% or more, 0.5000% or less, Sb: 0% or more, 0.0500% or less, As: 0% or more, 0.0500% or less, Mg: 0% or more, 0.0500 %, Ca: 0% or more and 0.0400% or less, Y: 0% or more and 0.0500% or less, La: 0% or more and 0.0500% or less, Ce: 0% or more and 0.0500% or less, Zr: 0% or more and 0.0500% or less, and the balance: Fe and impurities, and when the plate thickness is t, the metal structure at the t / 4 position, which is a position t / 4 from the surface of a cross section in the plate thickness direction, contains, by volume fraction, ferrite: 20% or more, bainite and martensite: a total of 40% or more, and the balance is one or more types selected from retained austenite and pearlite, and when the Mn concentration is measured at a plurality of measurement points at 1 μm intervals in a square region of the sheet thickness cross section centered at the t / 4 position and with one side having a length of t / 4, the proportion of measurement points where the Mn concentration is 1.1 times or more the average value of the Mn concentrations of all of the plurality of measurement points is less than 10.0%, the tensile strength is 980 MPa or more, and the product of tensile strength and total elongation is 10,500 MPa·% or more. [2] The steel plate according to [1] above has a chemical composition, in mass%, of Cr: 0.01% or more, 0.50% or less, Ni: 0.01% or more, 1.00% or less, Cu: 0.01% or more, 1.00% or less, Mo: 0.01% or more, 0.50% or less, Ti: 0.001% or more, 0.200% or less, Nb: 0.001% or more, 0.200% or less, V: 0.001% or more, 0.500% or less, B: 0.0001% or more, 0.0100% or less, W: 0.0005% or more, 0.1000% or less, Ta: 0.0005% or more, 0.1000% or less, and Sn: 0.0010% or more. , 0.0500% or less, Co: 0.0010% or more, 0.5000% or less, Sb: 0.0010% or more, 0.0500% or less, As: 0.0010% or more, 0.0500% or less, Mg: 0.0001% or more, 0.0500% or less, Ca: 0.0001% or more, 0.0400% or less, Y: 0.0001% or more, 0.0500% or less, La: 0.0001% or more, 0.0500% or less, Ce: 0.0001% or more, 0.0500% or less, and Zr: 0.0001% or more, 0.0500% or less. [3] The steel sheet according to the above [1] or [2] may have a hot-dip galvanized layer on the surface. [4] In the steel sheet according to the above item [3], the hot-dip galvanized layer may be a galvannealed layer. [5] A welded joint according to another aspect of the present invention is The method includes the steps of: forming a base material portion, a nugget portion, and a heat-affected zone;By mass%, C: 0.05% or more, 0.25% or less, Si: 0.05% or more, 2.00% or less, Mn: 1.50% or more, 3.00% or less, Al: 0.005% or more, 1.500% or less, P: 0% or more, 0.040% or less, S: 0% or more, 0.010% or less, N: 0% or more, 0.0100% or less, O: 0% or more, 0.0060% or less, Cr: 0% or more, 0.50% or less, Ni: 0% or more, 1.00% or less, Cu: 0% or more, 1.00% or less, Mo: 0% or more, 0.50% or less, Ti: 0% or more, 0.200% or less, Nb: 0% or more, 0.200% or less, V: 0% or more, 0.500 %, B: 0% or more and 0.0100% or less, W: 0% or more and 0.1000% or less, Ta: 0% or more and 0.1000% or less, Sn: 0% or more and 0.0500% or less, Co: 0% or more and 0.5000% or less, Sb: 0% or more and 0.0500% or less, As: 0% or more and 0.0500% or less, Mg: 0% or more and 0.0500% or less, Ca: 0% or more and 0.0400% or less, Y: 0% or more and 0.0500% or less, La: 0% or more and 0.0500% or less, Ce: 0% or more and 0.0500% or less, Zr: 0% or more and 0.0500% or less, and the balance: Fe and impurities, In the base material portion, when the thickness of the base material portion is t, a metal structure at a t / 4 position from the surface in a cross section in the thickness direction contains, in volume fraction, ferrite: 20% or more, bainite and martensite: a total of 40% or more, and the remainder is one or more types selected from retained austenite and pearlite, and when the Mn concentration is measured at a plurality of measurement points at 1 μm intervals in a square region of the cross section in the thickness direction, the length of one side of which is t / 4 and centered at the t / 4 position, the proportion of measurement points where the Mn concentration is 1.1 times or more the average value of the Mn concentrations of all the plurality of measurement points is less than 10.0%, The maximum value of the prior γ grain size in the heat affected zone is less than 30 μm. Effect of the Invention

[0010] According to the above aspect of the present invention, it is possible to provide a steel plate having excellent formability and a tensile strength of 980 MPa or more, which has sufficient welded joint strength after welding, and a welded joint obtained from the steel plate, which has sufficient welded joint strength. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a diagram illustrating the observation area of ​​the structure and the measurement area of ​​the Mn concentration in a cross section in the sheet thickness direction. [Diagram 2] FIG. 2 is a schematic diagram illustrating a heat-affected zone of a welded joint. [Diagram 3]11 is a histogram showing an example of Mn concentration distribution in the first segregation step when no holding at 1300° C. was performed (0 h) and when holding was performed for 10 hours (10 h). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] A steel sheet according to one embodiment of the present invention (steel sheet according to the present embodiment) (a) has a predetermined chemical composition, (b) when the thickness is t, a metal structure at a t / 4 position, which is a position t / 4 from the surface, in a cross section in the thickness direction contains, in volume fraction, 20% or more of ferrite, 40% or more in total of bainite and martensite, and the remainder is one or more types selected from retained austenite and pearlite, (c) when the Mn concentration is measured at a plurality of measurement points at 1 μm intervals in a square region of the cross section in the thickness direction, the region being centered at the t / 4 position and having a side length of t / 4, the proportion of measurement points where the Mn concentration is 1.1 times or more the average value of the Mn concentrations of all the plurality of measurement points is less than 10.0%, and (d) the tensile strength is 980 MPa or more, and the product of the tensile strength and total elongation is 10,500 MPa·% or more. Moreover, the welded joint according to this embodiment (A) has a predetermined chemical composition, and (B) the maximum value of the prior γ grain size in the heat affected zone is less than 30 μm. Each of these will be explained below.

[0013] 1. Steel plate First, the steel sheet according to this embodiment will be described. <Chemical composition> The chemical composition of the steel sheet according to this embodiment will be described below. The percentage of the content of each element is mass % unless otherwise specified.

[0014] C: 0.05% or more, 0.25% or less C (carbon) is an essential element for ensuring the strength of a steel sheet. By setting the C content to 0.05% or more, a desired high strength can be obtained. The C content may be 0.07% or more, or 0.08% or more. On the other hand, in order to ensure workability and weldability, the C content is set to 0.25% or less. The C content may be 0.23% or less, 0.22% or less, or 0.20% or less.

[0015] Si: 0.05% or more, 2.00% or less Silicon (Si) is an element that stabilizes ferrite. In other words, silicon increases the Ac3 point (Ac3 transformation point), making it possible to form a large amount of ferrite in a wide range of annealing temperatures, and is therefore included from the viewpoint of improving the structural controllability of the steel sheet. To obtain this effect, the Si content is set to 0.05% or more. On the other hand, in order to ensure the weldability of the steel plate, the Si content is set to 2.00% or less. The Si content may be 1.80% or less, 1.70% or less, or 1.50% or less.

[0016] Mn: 1.50% or more, 3.00% or less Mn (manganese) is a strong austenite stabilizing element and is an effective element for increasing the strength of steel sheets. To obtain these effects, the Mn content is set to 1.50% or more. The Mn content may be 1.60% or more or 1.70% or more. On the other hand, in order to ensure weldability and low temperature toughness, the Mn content is set to 3.00% or less. The Mn content may be 2.80% or less, 2.70% or less, or 2.50% or less.

[0017] Al: 0.005% or more, 1.500% or less Al (aluminum) is an element used for deoxidizing steel. To obtain this effect, the Al content is set to 0.005% or more. On the other hand, if Al is contained excessively, the effect becomes saturated and the cost increases unnecessarily, and the transformation temperature of the steel increases, increasing the load during hot rolling. Therefore, the Al content is set to 1.500% or less. The Al content is preferably 1.200% or less, 1.000% or less, or 0.800% or less.

[0018] P: 0% or more, 0.040% or less P (phosphorus) is a solid solution strengthening element and is effective in increasing the strength of steel plate, but excessive content deteriorates weldability and toughness. Therefore, the P content is set to 0.040% or less. The P content is preferably 0.035% or less, 0.030% or less, or 0.020% or less. The P content may be 0%, but reducing the P content to an extreme degree increases the dephosphorization cost. Therefore, from the viewpoint of economic efficiency, the P content may be set to 0.001% or more.

[0019] S: 0% or more, 0.010% or less S (sulfur) is an element contained as an impurity, and forms MnS in steel, which deteriorates toughness and hole expandability. Therefore, the S content is set to 0.010% or less as a range in which the deterioration of toughness and hole expandability is not significant. The S content is preferably 0.005% or less, 0.004% or less, or 0.003% or less. The S content may be 0%, but if the S content is reduced excessively, the desulfurization cost will be high. Therefore, from the viewpoint of economy, the S content may be set to 0.0001% or more.

[0020] N: 0% or more, 0.0100% or less N (nitrogen) is an element contained as an impurity, and when its content exceeds 0.0100%, it forms coarse nitrides in the steel, deteriorating its bendability and hole expandability. Therefore, the N content is set to 0.0100% or less. The N content is preferably 0.0080% or less, 0.0060% or less, or 0.0050% or less. The N content may be 0%, but if the N content is reduced too much, the cost of denitrification will be high. Therefore, from the viewpoint of economy, the N content may be set to 0.00010% or more.

[0021] O: 0% or more, 0.0060% or less O (oxygen) is an element contained as an impurity, and when its content exceeds 0.0060%, it forms coarse oxides in the steel, deteriorating the bendability and hole expandability. Therefore, the O content is set to 0.0060% or less. The O content is preferably 0.0050% or less or 0.0040% or less. The O content may be 0%, but from the viewpoint of manufacturing costs, the O content may be set to 0.0001% or more.

[0022] The basic chemical composition of the steel sheet according to this embodiment contains the above elements (basic elements), with the balance being Fe and impurities. Here, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of steel sheets, and are permissible within a range that does not adversely affect the present invention. However, the steel sheet may contain the following elements (optional elements) instead of part of Fe, if necessary. These elements do not necessarily have to be contained, so the lower limit is 0%. In addition, the following elements may be mixed in from raw material scrap, etc., but may be contained as impurities as long as the content is equal to or less than the upper limit described below.

[0023] Cr: 0% or more, 0.50% or less Ni: 0% or more, 1.00% or less Cu: 0% or more, 1.00% or less Cr (chromium), Ni (nickel) and Cu (copper) are all elements that contribute to improving strength. Therefore, one or more selected from these elements may be contained as necessary. To obtain the above effects, the content of one or more selected from Cr, Ni and Cu is preferably 0.01% or more, more preferably 0.10% or more. On the other hand, a Cr content of more than 0.50%, a Ni content of more than 1.00%, or a Cu content of more than 1.00% may deteriorate the pickling property, weldability, and hot workability. Therefore, the Cr content is 0.50% or less, the Ni content is 1.00% or less, and the Cu content is 1.00% or less. The Cr content may be 0.40% or less, 0.30% or less, or 0.10% or less. The Ni content may be 0.80% or less, 0.60% or less, or 0.20% or less. The Cu content may be 0.80% or less, 0.60% or less, or 0.20% or less.

[0024] Mo: 0% or more, 0.50% or less Mo (molybdenum), like Mn, is an element that improves the hardenability of steel and contributes to improving strength. Therefore, Mo may be contained as necessary. To obtain the above effects, the Mo content is preferably 0.01% or more, and more preferably 0.10% or more. On the other hand, if the Mo content exceeds 0.50%, the hot workability may deteriorate, and the productivity may decrease. Therefore, the Mo content is set to 0.50% or less. The Mo content is preferably 0.40% or less, 0.30% or less, or 0.10% or less.

[0025] Ti: 0% or more, 0.200% or less Nb: 0% or more, 0.200% or less V: 0% or more, 0.500% or less Ti (titanium), Nb (niobium) and V (vanadium) are all elements that contribute to improving the strength of steel sheets by precipitation strengthening, fine grain strengthening by inhibiting the growth of crystal grains, and dislocation strengthening through inhibiting recrystallization. Therefore, one or more elements selected from these elements may be contained as necessary. To obtain the above effects, it is preferable to contain one or more elements selected from 0.001% or more of Ti, 0.0001% or more of Nb, and 0.001% or more of V in the steel sheet. On the other hand, if the content of Ti exceeds 0.200%, if the content of Nb exceeds 0.200%, or if the content of V exceeds 0.500%, coarse carbonitrides may be precipitated, which may deteriorate the formability. Therefore, the Ti content is set to 0.200% or less, the Nb content is set to 0.200% or less, and the V content is set to 0.500% or less. The Ti content may be set to 0.180% or less, 0.150% or less, or 0.100% or less. The Nb content may be set to 0.180% or less, 0.150% or less, or 0.100% or less. The V content may be set to 0.400% or less, 0.300% or less, or 0.100% or less.

[0026] B: 0% or more, 0.0100% or less B (boron) is an element that segregates to the austenite grain boundary during welding to strengthen the grain boundary and contribute to improving the resistance to molten metal embrittlement cracking. Therefore, B may be contained as necessary. To obtain the above effects, the B content is preferably 0.0001% or more, more preferably 0.0005% or more or 0.0008% or more. On the other hand, if the B content exceeds 0.0100%, carbides and nitrides are generated, the above effects are saturated, and the hot workability is deteriorated. Therefore, the B content is set to 0.0100% or less. The B content is preferably 0.0080% or less, 0.0050% or less, or 0.0030% or less.

[0027] W: 0% or more, 0.1000% or less Ta: 0% or more, 0.1000% or less Sn: 0% or more, 0.0500% or less Co: 0% or more, 0.5000% or less As: 0% or more, 0.0500% or less W (tungsten), Ta (tantalum), Sn (tin), Co (cobalt), and As (arsenic) are elements that contribute to improving the strength of the steel sheet by suppressing precipitation strengthening and coarsening of crystal grains. Therefore, these elements may be contained. When the effect is obtained, the W content may be 0.0005% or more, 0.0010% or more, 0.0050% or more, or 0.0100% or more. The Ta content may be 0.0005% or more, 0.0010% or more, 0.0050% or more, or 0.0100% or more. The Sn content may be 0.0010% or more, 0.0020% or more, or 0.0050% or more. The Co content may be 0.0010% or more, 0.0100% or more, or 0.0300% or more. The As content may be 0.0010% or more, 0.0020% or more, or 0.0050% or more. On the other hand, if these elements are present in large amounts, the various properties of the steel sheet may be impaired. Therefore, the W content is set to 0.1000% or less, the Ta content is set to 0.1000% or less, the Sn content is set to 0.0500% or less, the Co content is set to 0.5000% or less, the Sb content is set to 0.0500% or less, and the As content is set to 0.0500% or less. The W content may be set to 0.0800% or less, 0.0500% or less, or 0.0300% or less. The Ta content may be set to 0.080% or less, 0.050% or less, or 0.0300% or less. The Sn content may be set to 0.0400% or less, 0.0300% or less, or 0.0100% or less. The Co content may be set to 0.4000% or less, 0.3000% or less, or 0.1000% or less. The As content may be 0.0400% or less, 0.0300% or less, or 0.0100% or less.

[0028] Mg: 0% or more, 0.0500% or less Ca: 0% or more, 0.0400% or less Y: 0% or more, 0.0500% or less La: 0% or more, 0.0500% or less Ce: 0% or more, 0.0500% or less Zr: 0% or more, 0.0500% or less Sb: 0% or more, 0.0500% or less Ca (calcium), Mg (magnesium), Y (yttrium), La (lanthanum), Ce (cerium), Zr (zirconium), and Sb (antimony) are all elements that contribute to improving formability. Therefore, one or more selected from these elements may be contained as necessary. In order to obtain the above effects, the content of one or more selected from Mg, Ca, Y, La, Ce, Zr, and Sb is preferably 0.0001% or more, or 0.0010% or more. The Sb content is more preferably 0.0020% or more, or 0.0050% or more. On the other hand, Mg, Y, La, Ce, Zr, Sb with a content exceeding 0.050%, or Ca with a content exceeding 0.040%, may deteriorate pickling property, weldability, and hot workability. Therefore, the contents of Mg, Y, La, Ce, Zr, and Sb are all set to 0.0500% or less, and the Ca content is set to 0.0400% or less. The contents of Mg, Ca, Y, La, Ce, Zr, and Sb are each preferably set to 0.0350% or less, 0.0300% or less, or 0.0100% or less.

[0029] As described above, the chemical composition of the steel sheet according to this embodiment includes basic elements with the balance being Fe and impurities, or includes basic elements and further includes one or more optional elements with the balance being Fe and impurities.

[0030] <When the plate thickness is t, the metal structure at the t / 4 position, which is the position t / 4 from the surface in the plate thickness direction cross section> [Ferrite: 20% by volume or more] Ferrite has excellent ductility but is a soft structure. To ensure the elongation of steel sheets, the volume fraction of ferrite is set to 20% or more. On the other hand, if the volume fraction of ferrite is excessive, it becomes difficult to ensure the desired strength of the steel sheet. Therefore, the volume fraction of ferrite is set to 60% or less. The volume fraction of ferrite may be 50% or less.

[0031] [Bainite and martensite: 40% or more by volume in total] To improve strength, the volume fraction of bainite and martensite is set to 40% or more in total. As long as this requirement is satisfied, the volume fractions of martensite and bainite do not need to be specified individually, but the tempered martensite content may be 10% or more, 15% or more, or 20% or more in volume fraction. The volume fraction of bainite and martensite is set to 80% or less in order to ensure 20% or more of ferrite. In the steel sheet according to this embodiment, the martensite includes fresh martensite and tempered martensite.

[0032] [Remainder: one or more selected from retained austenite and pearlite] The remainder other than ferrite, bainite, and martensite may include one or more selected from retained austenite and pearlite. The volume fraction of the remainder is, for example, 10% or less, or 5% or less. The volume fraction of the remainder may be 0%.

[0033] The volume fraction of martensite at the t / 4 position is determined by the following procedure. The observation surface of the sample is etched with a Lepera solution, and a 100 μm×100 μm area within 1 / 8 to 3 / 8 of the plate thickness from the surface, centered at 1 / 4 of the plate thickness from the surface of the plate thickness direction cross section as shown in FIG. 1A, is observed at a magnification of 3000 times using a FE-SEM. In Lepera corrosion, martensite and retained austenite are not corroded, so the area ratio of the uncorroded area is the total area ratio of martensite and retained austenite. In this embodiment, the total area ratio of martensite and retained austenite is considered to be the total volume ratio of these. The volume ratio of martensite is calculated by subtracting the volume ratio of retained austenite measured by a method described later from the area ratio (i.e., volume ratio) of the uncorroded area.

[0034] The volume fraction of retained austenite can be calculated by measurements using an X-ray diffractometer. In measurements using an X-ray diffractometer, first, the area from the plate surface (rolled surface) of the sample to a surface at a depth of 1 / 4 of the plate thickness is removed by mechanical and chemical polishing. Next, on the surface at a depth of 1 / 4 of the plate thickness t, MoKα rays are used as characteristic X-rays to determine the integrated intensity ratio of the diffraction peaks of (200), (211) of the bcc phase and (200), (220), and (311) of the fcc phase, and the volume fraction of retained austenite can be calculated based on these integrated intensity ratios.

[0035] The volume fractions of ferrite, bainite, and pearlite at the t / 4 position are determined by the following procedure. The observation surface of the sample is etched with a repeller solution, and a 100μm×100μm area is observed at a magnification of 3000x within a range of 1 / 8 to 3 / 8 of the plate thickness from the surface, centered at 1 / 4 of the plate thickness from the surface of the plate thickness direction cross section as shown in Figure 1A, using a FE-SEM. Regions that do not contain cementite in the crystals are judged as ferrite, regions that contain cementite in the crystals and where the cementite is arranged in a lamellar shape are judged as pearlite, and regions that contain cementite in the crystals and where the cementite has multiple variants are judged as bainite, and the area ratio is calculated by the point counting method (in accordance with ASTM E562). The area ratio and volume ratio are considered to be equivalent, and the obtained area ratio of each structure is taken as the volume ratio.

[0036] <When the Mn concentration is measured at multiple measurement points at 1 μm intervals in a square region with a side length of t / 4 centered at the t / 4 position on a cross section in the sheet thickness direction, the percentage of measurement points where the Mn concentration is 1.1 times or more the average value of the Mn concentrations at multiple measurement points (all measurement points): less than 10.0%> As described above, if coarse retained austenite or fresh martensite is present in the heat-affected zone, these become the starting points for cracks, which easily cause cracks to occur. In order to suppress such cracks, it is effective to refine the retained austenite (γ), but since coarse retained γ is generated in the Mn segregated area, it is effective to suppress Mn segregation. Specifically, when the Mn concentration is measured at multiple measurement points at 1 μm intervals using an EPMA (Electron Probe Micro Analyzer) in a square region with a side length of t / 4 centered at the t / 4 position in a cross section in the sheet thickness direction as shown in B in Figure 1, the proportion (number proportion) of measurement points where the Mn concentration is 1.1 times or more the average Mn concentration of all measurement points (multiple measurement points) (1.1 or more when the average value is 1.0) must be less than 10.0%. In other words, when the segregation degree is defined as "concentration at each measurement point / average concentration of all measurement points in the measurement region," the proportion where this segregation degree is 1.1 or more must be less than 10.0%.

[0037] <Mechanical properties> Considering that the steel plate according to this embodiment contributes to weight reduction of automobile bodies, the steel plate according to this embodiment has a tensile strength of 980 MPa or more. Moreover, the steel plate according to this embodiment has a tensile strength x total elongation (TS x tEl) of 10,500 MPa·% or more. The tensile strength (TS) and total elongation (tEl) are determined by taking a JIS No. 5 tensile test piece from the steel plate in the direction perpendicular to the rolling direction and conducting a tensile test in accordance with JIS Z 2241:2011.

[0038] [Plating layer] The steel sheet according to the present embodiment described above may have a hot-dip galvanized layer on the surface. The presence of the hot-dip galvanized layer on the surface improves corrosion resistance. For example, when a steel sheet is used in a corrosive environment, there are concerns about holes, etc., so even if the steel sheet is made stronger, it may not be possible to make the sheet thinner than a certain thickness. One of the purposes of increasing the strength of steel sheets is to reduce the weight by making them thinner, so even if a high-strength steel sheet is developed, if the corrosion resistance is low, the application sites are limited. For this reason, it is possible to apply a highly corrosion-resistant coating such as hot-dip galvanizing to the steel sheet. The coating layer is, for example, a zinc coating layer such as a hot-dip galvanizing layer or an electrolytic zinc coating layer. The zinc coating layer may also be a coating containing Si, Al and / or Mg in addition to Zn. The hot-dip galvanized layer may be an alloyed hot-dip galvanized layer, in which Fe is incorporated into the hot-dip galvanized layer by alloying treatment, and thus excellent weldability and paintability can be obtained. In addition, an upper layer of plating may be applied on the galvanized layer for the purpose of improving paintability and weldability. In addition, in the cold-rolled steel sheet according to the present embodiment, various treatments, such as chromate treatment, phosphate treatment, lubricity improvement treatment, weldability improvement treatment, etc., may be applied on the hot-dip galvanized layer.

[0039] 2. Welded joints Next, the welded joint according to this embodiment will be described. The welded joint according to the present embodiment is a welded joint obtained by welding the steel plate according to the present embodiment described above. Therefore, it has a base material portion, a nugget portion formed by welding, and a heat-affected zone formed around the nugget portion. The steel plate according to the present embodiment and another steel plate (which may be the steel plate according to the present embodiment) are joined via the nugget portion. The base material (excluding the heat-affected zone and the nugget zone) has the same chemical composition and metal structure as the steel plate according to the present embodiment. The heat-affected zone has the same chemical composition as the steel plate according to the present embodiment, but the metal structure is mainly martensite and has the following characteristics.

[0040] <Maximum prior gamma grain size in heat-affected zone: less than 30 μm> In order to reduce residual stress in the heat-affected zone of a welded joint, the maximum prior γ grain size, which corresponds to the block size of martensite, should be less than 30 μm. If the prior γ (austenite) grain size is 30 μm or more, residual stress will occur in the plate thickness direction, and cracks will easily occur in the vicinity of the grain size.

[0041] In the welded joint according to this embodiment, the heat-affected zone is defined as follows. As shown in Figure 2, in a welded joint having a nugget (nugget portion) N joining steel plates S and steel plates S, the hardness (Vickers hardness at a load of 0.1 kgf: performed in accordance with JIS Z 2244) is measured at a position on the steel plate overlapping surface side that is 1 / 4 of the plate thickness from the steel plate overlapping surface SF (in the figure, there is a gap between the steel plates S and the steel plates S, but they may be in close contact) in the plate thickness direction and within a range of 8 mm from the spot weld nugget center O in the plate thickness direction and perpendicular to the plate thickness direction (left and right on the page), and the transition region where the hardness is different from both the hardness of the nugget portion and the hardness of the base material portion (the same as the hardness of the steel plate before welding) is defined as the heat-affected zone (HAZ). The prior γ grain size is measured at a position 1 / 4 of the sheet thickness away from the steel sheet surface on the overlapping surface side, and at the center of the heat-affected zone in the direction perpendicular to the sheet thickness (left-right direction on the paper) using the following procedure. The observation surface of the sample is polished and then corroded with Nital reagent, and three fields of view are observed using an FE-SEM at 1000x magnification, with each field of view being 500μm x 500μm. The prior γ grain size is calculated using the line segment method using the obtained structural photograph. The average of the maximum prior γ grain sizes in each of the three visual fields observed is taken as the maximum prior γ grain size in the heat-affected zone.

[0042] [Joint strength] In the steel plate according to this embodiment, in consideration of weldability in the assembly of automobile bodies, it is preferable that the joint strength is more than 6.0 kN. The joint strength is determined by taking test pieces as specified in JIS Z 3137:1999 from the steel plate in a direction perpendicular to the rolling direction, welding them using a servo motor pressure type single-phase AC spot welder (power frequency 50 Hz), and then conducting a cross tensile test in accordance with JIS Z 3137:1999.

[0043] <Manufacturing method> The steel plate according to this embodiment can be manufactured by a manufacturing method including the following steps. (I) a first Mn segregation reduction step in which a slab obtained by continuous casting or the like is held at 1,300°C or higher for 5.0 hours or more and then cooled to 200°C or lower at an average cooling rate of 20°C / hour or more and 80°C / hour or less; (II) a second Mn segregation step of heating the slab and holding it at 1200° C. or higher for 1.0 hour or more; (III) a hot rolling step of hot rolling the slab after the second Mn segregation reducing step into a hot rolled steel sheet; (IV) a winding step of winding the hot-rolled steel sheet; (V) a cold rolling step of cold rolling the hot-rolled steel sheet after the coiling step to obtain a cold-rolled steel sheet; (VI) An annealing step of annealing the cold-rolled steel sheet. Moreover, the welded joint according to this embodiment can be produced by further subjecting the steel plate according to this embodiment obtained by the production method including (I) to (VI) to the following steps. (VII) Welding process for welding steel plates. Each step will be described below.

[0044] [First Mn segregation reduction process] In the first Mn segregation reduction step, a slab obtained by continuous casting or the like is held at 1,300°C or higher for 5.0 hours or more before the hot rolling step, and then cooled to 200°C or lower at an average cooling rate of 20°C / hour or more and 80°C / hour or less. By holding the slab at a high temperature of 1300°C or higher for 5.0 hours or more, the diffusion rate of Mn is increased and Mn segregation is reduced. However, this holding alone is not sufficient to reduce Mn segregation. Furthermore, it is necessary to cool the slab to 200°C or lower at an average cooling rate of 20°C / hour or more. By cooling the slab to 200°C or lower at an average cooling rate of 20°C / hour or more, dislocations due to thermal contraction differences are introduced. These dislocations become a high-speed diffusion path for Mn during heating in the next step, the second Mn segregation reduction step, so Mn can be diffused efficiently and the degree of Mn segregation is reduced. The faster the average cooling rate, the more dislocations are introduced. However, if the cooling rate is too fast, the thermal contraction difference becomes excessive, increasing the risk of slab cracking, so the average cooling rate is set to 80°C / hour or less. If the heating temperature is too high, the manufacturing cost increases, and if the heating time is too long, the productivity decreases. From these viewpoints, the heating temperature of the slab may be set to 1400°C or less, and the holding time at 1300°C or more may be set to 50.0 hours or less.

[0045] [Second Mn segregation reduction process] In the second Mn segregation reducing step, the slab after the first Mn segregation reducing step is heated to 1200° C. or higher in a heating furnace and held at that temperature range for 1.0 hour or more. By holding the slab at 1200°C or higher for 1.0 hour or more after the first Mn segregation step, Mn can be diffused by utilizing the dislocations introduced into the slab as a high-speed diffusion path, which further reduces Mn segregation. If the heating temperature is too high, the manufacturing cost increases, and if the heating time is too long, the productivity decreases. From these viewpoints, the heating temperature of the slab may be set to 1300°C or less, and the holding time at 1200°C or more may be set to 5.0 hours or less. This second Mn segregation reducing step may be performed in a hot rolling heating furnace as heating for hot rolling.

[0046] [Hot rolling process] In the hot rolling step, the slab that has been heated to 1200° C. or higher in the hot rolling heating furnace in the second Mn segregation reducing step and held for 1.0 hour or longer is subjected to hot rolling to obtain a hot rolled steel sheet. The hot rolling conditions are not particularly limited. For example, the finish rolling process may be completed at 800° C. or more and 980° C. or less, and then the steel sheet may be cooled to a coiling temperature of 600° C. or less at an average cooling rate of 2.5° C. / sec or more to a temperature of 600° C. or more and 750° C. or less.

[0047] [Winding process] [Cold rolling process] The hot-rolled steel sheet after the hot rolling process is coiled under known conditions to form a hot-rolled coil, and then cold-rolled under known conditions to form a cold-rolled steel sheet. For example, the total rolling reduction may be 20% or more and 85% or less.

[0048] [Annealing process] In the annealing process, in order to achieve a tensile strength of 980 MPa or more after the annealing process, the metal structure is annealed under conditions such that the ferrite volume fraction is 20% or more and the sum of the bainite volume fraction and martensite volume fraction is 40% or more. Specifically, a continuous annealing furnace or the like is used to heat a cold-rolled steel sheet to a soaking temperature of (Ac3-100)°C or more and less than 900°C, and the sheet is held at the soaking temperature for 5 to 600 seconds, and then cooled so that the average cooling rate in the temperature range of 500°C to 750°C is 2.5°C / sec or more and 30.0°C / sec or less. The cooling rate in the temperature range below 500°C is not particularly specified, and reheating or isothermal holding may be performed as long as the temperature is below 500°C. If the soaking temperature is low, austenite cannot be obtained, and the volume fraction of bainite and martensite cannot be sufficiently obtained by subsequent cooling. Therefore, the soaking temperature is set to (Ac3-100)°C or higher. On the other hand, if the soaking temperature is too high, the manufacturing cost increases, so the soaking temperature is preferably 900°C or lower. The soaking time is not limited, but if the soaking time is less than 5 seconds, austenitization may not proceed sufficiently. Therefore, the soaking time is preferably 5 seconds or more. On the other hand, if the soaking time exceeds 600 seconds, the productivity decreases, so the soaking time is preferably 600 seconds or less. If the average cooling rate from 500 to 750°C is 2.5°C / sec or less, the volume fraction of ferrite becomes too high, and the volume fractions of bainite and martensite cannot be sufficiently obtained. On the other hand, if the average cooling rate exceeds 50.0°C / sec, the volume fraction of ferrite cannot be sufficiently obtained. The Ac3 point is calculated in the following manner. Ac3(℃)=910-203×√[C]+44.7×[Si]-30×[Mn]+700×[P]-20×[Cu]-15.2×[Ni]-11×[Cr]+31.5×[Mo]+400×[Ti]+104×[V]+120×[Al] Here, [C], [Si], [Mn], [P], [Cu], [Ni], [Cr], [Mo], [Ti], [V] and [Al] are the contents (mass%) of each element contained in the slab.

[0049] [Hot-dip galvanizing process] [Alloying process] The cold-rolled steel sheet after the annealing step may be immersed in a hot-dip galvanizing bath to form a hot-dip galvanized steel sheet having a hot-dip galvanized layer on the surface. The hot-dip galvanized steel sheet may also be alloyed to form an alloyed hot-dip galvanized steel sheet. In this case, the temperature of the steel sheet can be maintained as described above by utilizing the heat applied to the steel sheet during hot-dip galvanizing and alloying. Known conditions can be applied to both processes.

[0050] [Welding process] The welded joint according to this embodiment is obtained by welding the steel plates according to this embodiment obtained by the above process. The welding conditions may be any known conditions, but an example of the welding conditions is a servo motor pressure type single-phase AC spot welding machine (power frequency 50 Hz), with an electrode diameter of 6 mm, welding pressure of 4 kN, welding current of 6.0 kA to 9.0 kA, current flow time of 0.4 seconds, and holding time of 0.1 seconds, so that the nugget diameter is 5√t (t: plate thickness). EXAMPLES

[0051] Slabs (steels Nos. A to Z) having the chemical compositions (units are mass %, the remainder being Fe and impurities) shown in Tables 1-1 and 1-2 were produced by continuous casting. These slabs were heated, held, and cooled to 200°C or lower as shown in Tables 2-1 and 2-2. The slab was then reheated and held as shown in Tables 2-1 and 2-2, and then hot rolled so that the finish rolling was completed at 800 to 980°C. The slab was then cooled to a coiling temperature of 600°C or less at an average cooling rate of 2.5°C / sec or more to a temperature of 600°C or more and 750°C or less, and coiled at 600°C or less to obtain a hot-rolled steel sheet of 2.0 to 4.0 mm. Furthermore, these hot rolled steel sheets were subjected to cold rolling at a rolling reduction of 20 to 85% to obtain cold rolled steel sheets having a thickness of 0.8 to 2.0 mm. These cold-rolled steel sheets were annealed under the conditions shown in Tables 2-1 and 2-2 (however, in the cases where the slabs were cracked, no processes subsequent to hot rolling were carried out). As shown in Tables 2-1 and 2-2, some of the cold-rolled steel sheets were subjected to hot-dip galvanizing, and further some of the cold-rolled steel sheets were subjected to alloying treatment.

[0052] Samples were taken from the obtained cold-rolled steel sheets (including plated steel sheets) in the manner described above, and the microstructures were observed to determine the volume fraction of ferrite, the total volume fraction of martensite and bainite, and the volume fractions of others (retained austenite and / or pearlite). Furthermore, the Mn concentration was measured using EPMA in the manner described above, and the ratio of measurement points where (measurement point concentration) / (average concentration of all measurement points in the measurement area) (i.e., segregation degree) was 1.1 or more was determined. The results are shown in Tables 3-1 and 3-2.

[0053] In addition, JIS No. 5 tensile test pieces were taken from the obtained cold-rolled steel sheets in a direction perpendicular to the rolling direction, and tensile tests were carried out according to JIS Z 2241:2011 to determine the tensile strength and total elongation. A material was judged to have high strength and excellent formability if its tensile strength (TS) was 980 MPa or more and its tensile strength × total elongation (TS × tEl) was 10,500 MPa·% or more. The results are shown in Tables 4-1 and 4-2.

[0054] In addition, test pieces described in JIS Z 3137:1999 were taken from the annealed cold-rolled steel sheets in a direction perpendicular to the rolling direction, and welding was performed using a servo motor pressure type single-phase AC spot welding machine (power frequency 50 Hz) with an electrode diameter of 6 mm, welding pressure of 4 kN, welding current of 6.0 kA to 9.0 kA, current flow time of 0.4 seconds, and holding time of 0.1 seconds, so that the nugget diameter was 5√t (t: plate thickness). Thereafter, a cross tensile test was performed in accordance with JIS Z 3137:1999 to determine the joint strength. If the joint strength was more than 6.0 kN, it was determined that the welded joint strength was excellent. The maximum value of the prior γ grain size in the heat affected zone of this welded joint was also determined in the above-mentioned manner. The results are shown in Tables 3-1, 3-2, 4-1, and 4-2.

[0055] [Table 1-1]

[0056] [Table 1-2]

[0057] [Table 2-1]

[0058] [Table 2-2]

[0059] [Table 3-1]

[0060] [Table 3-2]

[0061] [Table 4-1]

[0062] [Table 4-2]

[0063] As can be seen from Tables 1-1 to 4-2, the steel plates in the examples of the present invention all had excellent formability and tensile strengths of 980 MPa or more. Furthermore, in the welded joints obtained by welding these steel plates, the maximum prior γ grain size in the heat-affected zone was less than 30 μm, and the welded joint strength was also high. On the other hand, in the comparative examples in which at least one of the steel plates, the chemical composition, the volume fraction of each phase in the microstructure, the maximum grain size of retained austenite, and the proportion of measurement points where the segregation degree is 1.1 or more, did not satisfy the range of the present invention, one or more of the tensile strength and formability did not satisfy the target value, or in the welded joints obtained using these steel plates, the maximum value of the prior γ grain size was large and the welded joint strength was low. [Industrial Applicability]

[0064] According to the present invention, it is possible to provide a steel plate having excellent formability and a tensile strength of 980 MPa or more, which has sufficient welded joint strength after welding, and a welded joint obtained from the steel plate, which has sufficient welded joint strength, and thus has high industrial applicability. [Explanation of symbols]

[0065] A. Tissue observation area (100 μm × 100 μm area in the range of t / 8 to 3t / 8 centered at the t / 4 position) B. Measurement area of ​​Mn concentration (square area with one side of length t / 4 centered at the t / 4 position) t Plate thickness O Nugget Center N Nugget S steel plate (base material steel plate) SF Superimposed surface

Claims

1. In mass percent, C: 0.05% or more, 0.25% or less, Si: 0.05% or more, 2.00% or less, Mn: 1.50% or more, 3.00% or less, Al: 0.005% or more, 1.500% or less, P: 0% or more, 0.040% or less, S: 0% or more, 0.010% or less, N: 0% or more, 0.0100% or less, O: 0% or more, 0.0060% or less, Cr: 0% or more, 0.50% or less, Ni: 0% or more, 1.00% or less, Cu: 0% or more, 1.00% or less, Mo: 0% or more, 0.50% or less, Ti: 0% or more, 0.200% or less, Nb: 0% or more, 0.200% or less, V: 0% or more, 0.500% or less, B: 0% or more, 0.0100% or less, W: 0% or more, 0.1000% or less, Ta: 0% or more, 0.1000% or less, Sn: 0% or more, 0.0500% or less, Co: 0% or more, 0.5000% or less, Sb: 0% or more, 0.0500% or less, As: 0% or more, 0.0500% or less, Mg: 0% or more, 0.0500% or less, Ca: 0% or more, 0.0400% or less, Y: 0% or more, 0.0500% or less, La: 0% or more, 0.0500% or less, Ce: 0% or more, 0.0500% or less, Zr: 0% or more and 0.0500% or less, and Remainder: Fe and impurities having a chemical composition consisting of When the plate thickness is t, the metal structure at the t / 4 position, which is a position t / 4 from the surface in the plate thickness direction cross section, is expressed as the volume fraction: Ferrite: 20% or more, Bainite and martensite: 40% or more in total; The balance is one or more selected from retained austenite and pearlite, When the Mn concentration is measured at a plurality of measurement points at 1 μm intervals in a square region of the sheet thickness direction cross section, the region being centered at the t / 4 position and having a side length of t / 4, the proportion of measurement points at which the Mn concentration is 1.1 times or more the average value of the Mn concentrations at all of the plurality of measurement points is less than 10.0%, The tensile strength is 980 MPa or more, The product of tensile strength and total elongation is 10,500 MPa·% or more. steel plate.

2. The chemical composition, in mass%, Cr: 0.01% or more, 0.50% or less, Ni: 0.01% or more, 1.00% or less, Cu: 0.01% or more, 1.00% or less, Mo: 0.01% or more, 0.50% or less, Ti: 0.001% or more, 0.200% or less, Nb: 0.001% or more, 0.200% or less, V: 0.001% or more, 0.500% or less, B: 0.0001% or more, 0.0100% or less, W: 0.0005% or more, 0.1000% or less, Ta: 0.0005% or more, 0.1000% or less, Sn: 0.0010% or more, 0.0500% or less, Co: 0.0010% or more, 0.5000% or less, Sb: 0.0010% or more, 0.0500% or less, As: 0.0010% or more, 0.0500% or less, Mg: 0.0001% or more, 0.0500% or less, Ca: 0.0001% or more, 0.0400% or less, Y: 0.0001% or more, 0.0500% or less, La: 0.0001% or more, 0.0500% or less, Ce: 0.0001% or more and 0.0500% or less, and Zr: 0.0001% or more, 0.0500% or less, Contains one or more selected from the group consisting of The steel sheet according to claim 1.

3. The surface has a hot-dip galvanized layer. The steel sheet according to claim 1 or 2.

4. The hot-dip galvanized layer is a galvannealed layer. The steel sheet according to claim 3.

5. A base metal portion, a nugget portion, and a heat-affected zone, The base material portion is, in mass%, C: 0.05% or more, 0.25% or less, Si: 0.05% or more, 2.00% or less, Mn: 1.50% or more, 3.00% or less, Al: 0.005% or more, 1.500% or less, P: 0% or more, 0.040% or less, S: 0% or more, 0.010% or less, N: 0% or more, 0.0100% or less, O: 0% or more, 0.0060% or less, Cr: 0% or more, 0.50% or less, Ni: 0% or more, 1.00% or less, Cu: 0% or more, 1.00% or less, Mo: 0% or more, 0.50% or less, Ti: 0% or more, 0.200% or less, Nb: 0% or more, 0.200% or less, V: 0% or more, 0.500% or less, B: 0% or more, 0.0100% or less, W: 0% or more, 0.1000% or less, Ta: 0% or more, 0.1000% or less, Sn: 0% or more, 0.0500% or less, Co: 0% or more, 0.5000% or less, Sb: 0% or more, 0.0500% or less, As: 0% or more, 0.0500% or less, Mg: 0% or more, 0.0500% or less, Ca: 0% or more, 0.0400% or less, Y: 0% or more, 0.0500% or less, La: 0% or more, 0.0500% or less, Ce: 0% or more, 0.0500% or less, Zr: 0% or more and 0.0500% or less, and Remainder: Fe and impurities having a chemical composition consisting of In the base material portion, When the thickness of the base material portion is t, a metal structure at a t / 4 position, which is a position t / 4 from the surface of a cross section in the thickness direction, contains, by volume fraction, ferrite: 20% or more, bainite and martensite: 40% or more in total, and the balance is one or more types selected from retained austenite and pearlite, When the Mn concentration is measured at a plurality of measurement points at 1 μm intervals in a square region of the sheet thickness direction cross section, the region being centered at the t / 4 position and having a side length of t / 4, the proportion of measurement points at which the Mn concentration is 1.1 times or more the average value of the Mn concentrations at all of the plurality of measurement points is less than 10.0%, The maximum value of the prior γ grain size in the heat-affected zone is less than 30 μm; Welded joint.

Citation Information

Patent Citations

  • Tmimethyl siloxane steroid intermediate

    JP1978005149A

  • Hot rolled steel plate excellent in fatigue characteristic and it production

    JP1994128688A

  • Steel for crude oil tank, its production method, crude oil tank and its corrosion prevention method

    JP2004204344A

  • Method for producing high strength cold-rolled steel sheet having excellent impact property and shape-fixability

    JP2004300452A

  • Steel sheet and method for manufacturing the same

    JP2009221519A